Empirical Evidence of Banking Risk Management in Indonesia - Nabila, Nabila; Kusmayadi, Iwan (Indonesian Journal of Advanced Research, 2025)
This study aims to analyze the differences in banking risk in Indonesia before and after the implementation of POJK No. 18/POJK.03/2016 concerning Risk Management for Commercial Banks. This study contributes to society and the banking world by increasing understanding of the importance of implementing risk management in maintaining the stability of the national financial system. The present research employs a comparative quantitative approach to analyze the differences in banking risk before and after the implementation of the POJK. Data collection was conducted utilizing secondary data obtained from bank financial reports and official OJK publications during the period 2009–2024. The findings of the research indicate significant differences in the NPL, BOPO, and NIM variables, while the LDR ratio does not show a significant difference with a significance level above 0.05. These findings provide a new perspective on the effectiveness of risk management regulatory policies in Indonesia.